Distributions of successions of arbitrary multisets - Kong, Yong (Communications in statistics. Theory and methods, 2022)
By using the matrix formulation of the two-step approach to distributions of patterns in random sequences, recurrence and explicit formulas for the generating functions of successions in random permutations of arbitrary multisets are derived. Explicit formulas for the mean and variance are also obtained.